Rethinking Basic Writing : Exploring Identity, Politics, and Community in Interaction. - Gray-Rosendale, Laura (Taylor & Francis, 1999)
This book surveys the history of basic writing scholarship, suggesting that we cannot adequately theorize the situations of basic writers unless we examine how they construct their own conceptions of their identities, their constructions of their relation.